Pengukuran Tingkat Kepuasan Mahasiswa Terhadap Layanan Perguruan Tinggi Menggunakan Analytic Network Process: Studi Kasus Universitas Bakrie - Herawan, Didit; Citra, Fatma (Business and Management Review, 2011)
In the higher education sector, student satisfaction is one of key indicators in measuring quality of a college. The level of student satisfaction depends on many factors influencing it, which may varies among colleges. This study, conducted in 2011, measured the student satisfaction of Bakrie University and the level of importance of each influencing factor using Analytic Network Process, a decision support system tool. Analytic Network Process was considered a new tool for this purpose. There were seven influencing factors identified in the study. The result showed overall level of student satisfaction of 79.3%. The most influencing factor was the service quality of academic faculty, while the least influencing factor was the service quality of non-academic staffs. Key word: student satisfaction, customer satisfaction, Analytic Network Process.